Femtosecond laser-assisted anterior lamellar keratoplasty for the treatment of stromal corneal pathology - Lu, Yan (BMC Ophthalmol, 2015)
BACKGROUND: To describe the initial outcomes and safety of anterior lamellar keratoplasty (ALK) assisted by a femtosecond laser for stromal corneal pathology. METHODS: A non-comparative case series of 14 eyes (13 patients) with various stromal corneal diseases underwent ALK with a femtosecond laser. Femtosecond laser settings, technique, uncorrected visual acuity (UCVA), best-corrected visual acuity (BCVA), and endothelial cell density (ECD) were measured. RESULTS: All eyes were successfully treated without intraoperative complications. The UCVA improved in 11 eyes (78.6%) compared with preoperative UCVA. The mean difference between preoperative and postoperative UCVA was a gain of 1.7 lines (range, unchanged to 6 lines). The BCVA improved in all eyes compared with preoperative levels. The mean difference between preoperative and postoperative BCVA was a gain of 2.4 lines (range, 1–8 lines). In 3 eyes, phototherapeutic keratectomy was performed. The mean reduction in endothelial cell density was 3.7% after a mean 7.3 months of follow-up. No graft rejection, infection, or epithelial ingrowth was found. CONCLUSIONS: Femtosecond laser-assisted ALK improved UCVA and BCVA in patients with stromal corneal pathology. Our early results indicated that the femtosecond laser produced an effective and smooth dissection through opaque corneas even deeper corneal tissue.